KEPEMIMPINAN KEPALA SEKOLAH DALAM MENANGKAL RADIKALISME DI SEKOLAH MENENGAH PERTAMA BAHRUL MAGHFIROH MALANG - Jefry Hadi Susilo Ramadan; Maskuri Maskuri; Mutiara Sari Dewi (VICRATINA, 2020)
Today, the rapid-current post-reformation marked the opening of a very free democratic faucet. This opens the way for the hard flow of religious affairs, this flow that does not conform to the philosophy of the Indonesian nation. The flow was radicalism. The school became one of the target of hard groups on behalf of religions. The school is headed by the headmaster, the school principal is required to use his power to ward off the movement, the importance of the school principal in ward against the flow of radicalism, through its leadership way. This study aims to describe the type of leadership, the design done, the implementation of the school principal and the leadership model of the college principal in the ward against radicalism in SMP Bahrul Maghfiroh Malang. This research uses a qualitative approach. Data retrieval is taken with structured interviews, observation structures, documentation.